Implementasi Struktur Aljabar Dalam Persilangan Golongan Darah - Fakhry Asad Agusfrianto; Gusti Ayu Dwi Yanti; Irnawati Dau (Program Studi Matematika Universitas Negeri Jakarta, 2023)
In the study of algebraic structures, the basic object of mathematics, namely sets, can be given abstract structures such as groups or rings. In this paper, we will study the algebraic structure found in crosses between two individuals with blood groups using the ABO, Rhesus, and MN systems.